2014
DOI: 10.1080/02699931.2013.878687
|View full text |Cite
|
Sign up to set email alerts
|

Confusion of fear and surprise: A test of the perceptual-attentional limitation hypothesis with eye movement monitoring

Abstract: Of the basic emotional facial expressions, fear is typically less accurately recognised as a result of being confused with surprise. According to the perceptual-attentional limitation hypothesis, the difficulty in recognising fear could be attributed to the similar visual configuration with surprise. In effect, they share more muscle movements than they possess distinctive ones. The main goal of the current study was to test the perceptual-attentional limitation hypothesis in the recognition of fear and surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 19 publications
14
39
1
Order By: Relevance
“…Goeleven et al, 2008;Langner et al, 2010) might be due to the visual similarities in those two emotions since both involve equal eye-muscle action units: raised eyebrows and upper lids. This explanation has been investigated as the perceptual-attentional limitation hypothesis, proposing that the confusion of fear and surprise comes forth of a failure to perceive differences between the expressions, and if the cues are perceived, not enough attention is directed towards these facial features (Roy-Charland, Perron, Beaudry, & Eady, 2014). A study that manipulated distinctiveness and attention found support for both components of the hypothesis (Chamberland, Roy-Charland, Perron, & Dickinson, 2017), and the current results fit with this explanation as well.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Goeleven et al, 2008;Langner et al, 2010) might be due to the visual similarities in those two emotions since both involve equal eye-muscle action units: raised eyebrows and upper lids. This explanation has been investigated as the perceptual-attentional limitation hypothesis, proposing that the confusion of fear and surprise comes forth of a failure to perceive differences between the expressions, and if the cues are perceived, not enough attention is directed towards these facial features (Roy-Charland, Perron, Beaudry, & Eady, 2014). A study that manipulated distinctiveness and attention found support for both components of the hypothesis (Chamberland, Roy-Charland, Perron, & Dickinson, 2017), and the current results fit with this explanation as well.…”
Section: Discussionsupporting
confidence: 74%
“…Also, children have less experience in enacting emotions, while this experience in the form of mimicry has been shown to facilitate explicit emotion recognition (Conson et al, 2013). The hit rates showing differentiation between positive and negative emotions, but confusions between conceptually similar emotions, are in line with Bullock and Russell's (1984) differentiation account and the perceptual-attentional limitation hypothesis (Roy-Charland et al, 2014). This implies that when creating stimulus materials for school-aged children, pictures of emotions that are highly similar either conceptually or in how they are physically expressed (e.g.…”
Section: Discussionsupporting
confidence: 54%
“…With this space-by-time manifold decomposition, we address important questions in emotion communication using facial expressions. In particular, we determine which synergistic facial movements communicate emotions, and we isolate the specific movements that cause confusions between specific emotion categories (e.g., fear and surprise; see Ekman, 1992 ; Gagnon, Gosselin, Hudon-ven Der Buhs, Larocque, & Milliard, 2010 ; Jack, Blais, Scheepers, Schyns, & Caldara, 2009 ; Matsumoto & Ekman, 1989 ; Moriguchi et al, 2005 ; Roy-Charland, Perron, Beaudry, & Eady, 2014 ) from those that resolve these confusions. That is, we can identify the low-dimensional space-by-time representation that predicts categorization behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Fear and surprise can cause confusion in recognition due to similar configuration of the facial muscles, according to the perceptual–attentional limitation hypothesis. Roy‐Charland, Perron, Beaudry, and Eady () found out that accuracy of fear recognition can be lower than that of surprise when distinctive cues are visible only in the eyebrows. Confusion between anger and disgust has been reported in individuals with Huntington's disease (Calder et al, ) and reduced sensitivity in their recognition has been reported in social anxiety disorder (Montagne et al, ).…”
Section: Discussionmentioning
confidence: 99%